Distributed series resistance in a one-dimensional two-diode model revisited. (September 2017) - Wagner, Jan-Martin; Rißland, Sven; Schütt, Andreas; Carstensen, Jürgen; Adelung, Rainer
Abstract: The lumped series resistance R s of large-area silicon solar cells, obtained from current–voltage ( I–U ) data according to the two-light-level method, varies along the I–U characteristic. Such a variation can most simply be described by the linear-response series resistance model (LR- R s ), recently developed in connection with luminescence imaging. Here, independently obtained experimental data are used to test the applicability of the LR- R s model to R s data based on I–U characteristics. After subtracting a non-distributed part from the measured R s data, the inverse of the remaining distributed part shows a scaling proportional to the inverse of the bias-dependent diode resistance; a slope value of 1 is used as predicted by the LR- R s model applied to a laterally one-dimensional geometry. The same experimental data have previously been interpreted based on a mathematically rather complicated model published already many years ago; just recently it was found that in some cases this model may lead to unphysical results. The present LR- R s model based proper interpretation of the variation of the lumped series resistance along the I–U characteristic leads to a roughly half-by-half splitting between the distributed and the non-distributed part of R s . This share has been observed many years for "economically reasonable" solar cells investigated by the CELLO technique. The successful usage of the LR- R s model for I–U based R s data is a strong hint that its underlying physical concepts are of general validity.